Woordeboek en gebruik: 'n bose kringloop - Prinsloo, A.F. (Lexikos, 1991)
Dictionary and Usage: A Vicious Circle This study examines the statement that the practice of compiling Afrikaans explanatory and translating dictionaries by excerpting from published material has created a vicious circle that results in the exclusion from dictionaries of lexical items regarded as standard language by educated mother-tongue speakers of Afrikaans. The reason for this is that language in excerpted publications (books, magazines, newspapers) is usually sub-edited to a greater or lesser degree by language practitioners who in turn follow the prescriptions of dictionaries. The result is a vicious circle that is entrenched further by lexicographical standardizing techniques such as exclusion or negative labelling. The three main issues discussed in the study are (a) prescriptions to the prescribers (lexicographers); (b) the treatment of sixteen lexical items in dictionaries and language manuals; (c) results of an empirical investigation of these sixteen cases among five groups of educated mother-tongue speakers (102 respondents in all). The conclusion is that Afrikaans explanatory and translating dictionaries do not yet reflect the usage of these cases (and by implication many others).